Forensic Handwriting Analysis by Digital Photographic Copies of Documents (Part 2) - M. V. Zhizhina (Теория и практика судебной экспертизы)
The article presents the results of the second stage of the development of methodological guidelines for the forensic handwriting research of handwriting objects in digital copies of documents. This publication is a continuation of the article from 2020 [1].The author discusses some technological aspects of digital photographing and scanning, as well as technical characteristics of a digital photograph (scan), offers general conceptual clarifications related to the study of handwriting implementations in digital copies of documents; defines the qualitative characteristics of handwriting objects that determine the admissibility of handwriting research and presenting efficient conclusions; lists the factors reducing the quality indicators of digital images, and signs pointing to them; proposes the rules and conditions for digital copying of documents for the most optimal quality of handwriting objects in order to conduct identification and diagnostic studies; considers the algorithms of actions for a handwriting expert when working with images of digital handwriting objects submitted for research in the form of a computer file.